Blended Learning in Counseling Laboratory Techniques (CLT) Courses: Student Perceptions About the Effectiveness of Learning - Muhammad Putra Dinata Saragi; Abdurrahman Abdurrahman; Rina Suryani (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
The learning system regularly undergoes changes that require instructors and learners to utilize electronic media and online networks to carry out the learning process, with the hope that learning can be more productive. This study aims to analyze students' perceptions of learning that combine conventional methods and online methods, as well as see their effectiveness in laboratory-based courses. This study used 165 students as a sample and 15 students as participants for semi-structured interviews. Data were collected using a closed questionnaire that has been tested for validity and reliability and interviews. The research findings show that students' perceptions of blended learning in the effective category and active blended learning contribute to students in learning. The findings of this study can be input in improving the quality of learning in higher education and improving graduate achievement